Microfluidics flow and heat transfer in microstructured fibers of circular and elliptical geometry - Christodoulides, Paul; Florides, Georgios A.; Davies, Edward M.; Kalli, Kyriacos; Dias, Frederic (My University, 2015)
The field of microfluidics utilizes micron-scale devices to control the flow of fluids. The principal application is the manipulation of very small volumes of fluids on the order of nanoliters to femtoliters that are typically seeded with nanoparticles. Hence the control and sorting of nanoparticles is a primary goal using this technology. There is recent interest in the use of microstructure optical fibers for many applications that are principally related to optical sensing and new forms of optical spectroscopy as part of this, knowledge of the heat transfer of fluids, whereby the guided light interacts with a fluid in the region of the air-hole structure, demands special attention. In this work we study the fluid transport capabilities of microstructured fibers with cross-sections containing circular or elliptical holes, while considering the effects of flow rates, fluid viscosity, and the channel shape. The role of heat flux is considered in relation to the fluid characteristics. Results can be obtained through the solution of the time-dependent Navier-Stokes equations and the convection-diffusion equation. This work is of importance as one cannot assume that the flow dynamics in microstructured fibers will be the same as conventional microfluidic channels. Through the study of the heat transfer, for pressure-driven and other flows and for low Reynolds numbers, we confirm the anticipated behavior of the fluids in the microchannel structure.
Keywords: Flow dynamics; Fluid transport; Heat flux; Heat transfer; Microfluidics; Nanoparticles; Optical spectroscopy